Protein stoichiometry, structural plasticity and regulation of bacterial microcompartments. (October 2021) - Liu, Lu-Ning; Yang, Mengru; Sun, Yaqi; Yang, Jing
Graphical abstract: Highlights: Bacterial microcompartments (BMCs) are self-assembling organelles comprising a protein shell that encapsulates cargo enzymes. Unraveling the composition and stoichiometry of BMC components is key for understanding BMC assembly and bioengineering. The protein stoichiometry and structures of BMCs are modular. The structural plasticity of BMCs provides the foundation for modulating shell permeability, BMC assembly and function. BMC biosynthesis and functions are actively regulated in native host cells. Abstract : Bacterial microcompartments (BMCs) are self-assembling prokaryotic organelles consisting of a polyhedral proteinaceous shell and encapsulated enzymes that are involved in CO2 fixation or carbon catabolism. Addressing how the hundreds of building components self-assemble to form the metabolically functional organelles and how their structures and functions are modulated in the extremely dynamic bacterial cytoplasm is of importance for basic understanding of protein organelle formation and synthetic engineering of metabolic modules for biotechnological applications. Here, we highlight recent advances in understanding the protein composition and stoichiometry of BMCs, with a particular focus on carboxysomes and propanediol utilization microcompartments. We also discuss relevant research on the structural plasticity of native and engineered BMCs, and the physiological regulation of BMC assembly, function and positioning in native hosts.